PEMANFAATAN INFORMASI AKUNTANSI MANAJEMEN DALAM PENENTUAN HARGA TRANSFER AFILIASI - Ahmad Haris Hidayatullah; Dutri Novharisa Pakpahan; Chiara Choiri Anora; Sutan Aziz Harahap; Tiolina Evi (Bajang Institute, 2025)
Following the enactment of PMK-213/PMK.03/2016, which was subsequently replaced by PMK-172 of 2023, taxpayers are required to prepare transfer pricing documentation at the time the transaction occurs (ex ante). However, in practice, many entities or companies only establish their transfer pricing documentation after the transaction has occurred (at the end of the tax year), a method referred to as ex post. For this study, the researcher examined audit results from KPP Madya Karawang, two tax court decisions (PUT-006992.15/2023/PP/M.XIB of 2024 and PUT-011382.15/2023/PP/M.IXA of 2024), and conducted interviews with several tax auditors. These auditors had served at KPP Madya Bekasi, KPP Madya Karawang, KPP PMA Satu, KPP PMA Tiga, KPP Madya Batam, and the Directorate of Audit and Collection at the Directorate General of Taxes Head Office.The study results indicate that taxpayers failed to implement transfer pricing documentation ex ante, which is inconsistent with domestic regulations. Despite having the necessary management accounting data and information to create transfer pricing policies, taxpayers still opted for an ex post basis. Furthermore, taxpayers were reluctant to disclose transfer pricing policy information because of its sensitive and confidential nature. In the ex ante price setting approach, particularly for manufacturing companies, entities are mandated to disclose their transfer pricing policies. When these policies are not clearly disclosed, conducting the price setting approach becomes difficult. Ultimately, the two tax judges' decisions reviewed were in alignment with the applicable regulations.